The Culture Of Paternalism, The Role Of Women In Kek, And Women Politics In The Time Of The Covid-19 Pandemic - Renny Nurhasana; Tio Massa Elnitin Sianipar (Jurnal Syntax Transformation, 2020)
The turmoil of political reform provided significantopportunities for women in Indonesia compared to theprevious condition where their political rights were still verylimited. Movements emerged in the form of efforts toempower women's rights, especially destructive politicalrights. Although this reform era could not eliminate apathyand the inability of women to be included in the hegemonicand repressive political system for decades, on the other hand,the role of women in maintaining family economic resilienceis quite strategic, because the role of women in communitydevelopment both in urban and rural areas shall continue to beimproved in the results implementation of its development,quality development of human resources, and maintenance ofthe environment. The theory used in this research is related tothe Paternalistic Culture, the Role of Women in KEK, andPolitics. This research explains that indicators of developmentin the political field have progressed in their achievements insuch way that women may fall behind in gaining egalitarianopportunities with men. Legislation shall be utilized in thecreation of women’s participation in political parties and theHouse of Representatives (DPR) to accommodate theformulation of robust democratic political culture based on theperspective of equality between men and women